A proposta de governo como elemento do discurso político e a (in)definição das políticas públicas no processo eleitoral democrático brasileiro - Andrade, Luciano Pereira (2023)
This work focuses on a critical analysis of constitutional democracy in Brazil, especially about the (in)definition of public policies in the electoral process. The aim is to investigate the relationship between the Brazilian electoral system and the speeches contained in government programs, a legal requirement for all executive candidates, to verify whether they reflect the constitutional possibilities of the position they intend to hold. This is because, currently, the political discourse in government programs is predominantly formal and centered on the candidate’s image, without the program presenting/representing substantial governance or, often, concrete proposals for the realization of fundamental human rights embodied in public policies. To this end, brief notes will be made on contemporary democracy, as well as the way in which the circulation of political discourses present in the government programs of the candidates for the head of the Federal Executive Branch in the years 2018 and 2022 that advanced to the second round, to identify the ideological load and concrete density of the proposals, indicating their eventual constitutional limits. Next, the objective guidelines for the formulation of public policies will be outlined, based on the foundations and objectives of the Constitution of the Federative Republic of Brazil, then a comparison will be made with the candidates’ proposals in order to analyze whether they are compatible, not only with the Constitution, but also with the regime of administrative acts and, finally, the current position of the Judiciary in the effectiveness and guarantee of the protection of fundamental rights with the turn propitiated by neoconstitutionalism, measuring it, with constitutionalism of the future, in order to reveal the judicial enforcement of content, if necessary. The work will be carried out, therefore, based on a bibliographical review and elements of discourse analysis for the confrontation of government programs with the constitutional possibilities of implementing the proposals.